NF-κB Function in Growth Control: Regulation of Cyclin D1 Expression and G(0)/G(1)-to-S-Phase Transition - Hinz, Michael (American Society for Microbiology, 1999)
Nuclear factor kappa B (NF-κB) has been implicated in the regulation of cell proliferation, transformation, and tumor development. We provide evidence for a direct link between NF-κB activity and cell cycle regulation. NF-κB was found to stimulate transcription of cyclin D1, a key regulator of G(1) checkpoint control. Two NF-κB binding sites in the human cyclin D1 promoter conferred activation by NF-κB as well as by growth factors. Both levels and kinetics of cyclin D1 expression during G(1) phase were controlled by NF-κB. Moreover, inhibition of NF-κB caused a pronounced reduction of serum-induced cyclin D1-associated kinase activity and resulted in delayed phosphorylation of the retinoblastoma protein. Furthermore, NF-κB promotes G(1)-to-S-phase transition in mouse embryonal fibroblasts and in T47D mammary carcinoma cells. Impaired cell cycle progression of T47D cells expressing an NF-κB superrepressor (IκBαΔN) could be rescued by ectopic expression of cyclin D1. Thus, NF-κB contributes to cell cycle progression, and one of its targets might be cyclin D1.